L’après-inscription du gwoka sur la Liste du Patrimoine Culturel Immatériel de l’UNESCO : entretien avec Gabriel Mugerin, Patrick Solvet et Rosan Monza, membres du centre Rèpriz (Guadeloupe) - Pierre-Eugène Sitchet (Transposition)
Founded by Félix Cotellon in 2005, Rèpriz, the Centre for Traditional and Popular Music and Dances of Guadeloupe, conducted a series of actions leading to the inscription of gwoka music on UNESCO's Representative List of the Intangible Cultural Heritage (ICH) of Humanity in 2014.This interview is based on a conversation with three Rèpriz board members, Gabriel Mugerin, Patrick Solvet and Rosan Monza, in which they recall the process of determining the discourse used to explain the legitimacy of their approach with UNESCO to the community. They also address questions raised by the concept of intangibility in the case of heritage that is at first sight very tangible. They shed light on their understanding of the notion of “intangible heritage” and examine underlying issues with regard to the inscription and its effects observed four years later.